Back Cover. Issue 7 (13th June 2020) - Unknown
Abstract : Two‐dimensional (2D) transition metal dichalcogenides (TMDs) usually have poly‐phases, such as 2H, 3R and 1T. Controlling the structure phase of 2D TMDs is the key for engineering the physical and chemical properties of the materials and hence is vital to the applications. Many approaches, including doping/intercalation, alloying, defects, strain, electric field and so on, have been developed to tune the thermodynamic stability of the different phases of TMDs and then phase selective synthesis or controlled phase conversion has been achieved. More details are discussed in the article by Xie et al . on page 753–760. Abstract : Two‐dimensional (2D) transition metal dichalcogenides (TMDs) usually have poly‐phases, such as 2H, 3R and 1T. Controlling the structure phase of 2D TMDs is the key for engineering the physical and chemical properties of the materials and hence is vital to the applications. Many approaches, including doping/intercalation, alloying, defects, strain, electric field and so on, have been developed to tune the thermodynamic stability of the different phases of TMDs and then phase selective synthesis or controlled phase conversion has been achieved. More details are discussed in the article by Xie et al . on page 753–760.